China in Global Lithium Production: A Study on Economic Viability - Utkina Margarita Sergeevna (Fakultas Ekonomi dan Bisnis Islam, 2025)
The study aims to analyze China's strategic role in global lithium production amid increasing demand for critical minerals to support the energy transition. The background of this study is based on the limitations of China's domestic lithium reserves, while the country is able to dominate the downstream sector through processing and refining. The research uses a descriptive-analytical approach with secondary data sourced from USGS, IEA, UN Comtrade, as well as academic and official policy publications for the 2019–2023 period. The analysis was conducted comparatively to compare China's production, import and investment capacity with other major producing countries. The results show that China's dominance is more determined by its mastery of downstream technology, vertical integration, and global investment strategies than by the availability of domestic reserves. Expansion into Latin America and Africa through the acquisition of lithium mines is a key instrument in securing the supply of raw materials. The contribution of this research lies in the synthesis of the literature on mineral geopolitics by highlighting the paradox between resource limitations and the dominance of downstream industries. These findings have important implications for other countries in formulating energy security strategies, supply diversification, and downstream policies in the transition era to clean energy.